Gut metabolite Urolithin A mitigates ionizing radiation‐induced intestinal damage. Issue 21 (1st October 2021) - Zhang, Yuanyang; Dong, Yinping; Lu, Ping; Wang, Xinyue; Li, Wenxuan; Dong, Hui; Fan, Saijun; Li, Deguan
Abstract: Ionizing radiation (IR)‐induced intestinal damage is the major and common injury of patients receiving radiotherapy. Urolithin A (UroA) is a metabolite of the intestinal flora of ellagitannin, a compound found in fruits and nuts such as pomegranates, strawberries and walnuts. UroA shows the immunomodulatory and anti‐inflammatory capacity in various metabolic diseases. To evaluate the radioprotective effects, UroA(0.4, 2 and 10 mg/kg) were intraperitoneally injected to C57BL/6 male mice 48, 24, 1 h prior to and 24 h after 9.0Gy TBI. The results showed that UroA markedly upregulated the survival of irradiated mice, especially at concentration of 2 mg/kg. UroA improved the intestine morphology architecture and the regeneration ability of enterocytes in irradiated mice. Then, UroA significantly decreased the apoptosis of enterocytes induced by radiation. Additionally, 16S rRNA sequencing analysis showed the effect of UroA is associated with the recovery of the IR‐induced intestinal microbacteria profile changes in mice. Therefore, our results determinated UroA could be developed as a potential candidate for radiomitigators in radiotherapy and accidental nuclear exposure. And the beneficial functions of UroA might be associated with the inhibition of p53‐mediated apoptosis and remodelling of the gut microbes.